IMPLEMENTASI PENERAPAN FUNGSI NONLINER DALAM MATEMATIKA EKONOMI PADA KEHIDUPAN SEHARI-HARI: Implementation Of The Application Of Nonlinear Functions In Mathematics Economics In Daily Life - Parida, Parida; Melisa, Melisa; Safitri, Mardiana; Zakiah, Nina (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
This research aims to dig deeper into the implementation of nonlinear functions in economic mathematics in everyday life. Nonlinear functions in economics have become an increasingly popular research topic in recent decades, with wide applications in various fields, including macro and microeconomics, finance, and business. This research uses qualitative methods with literature review techniques. In this method, data is collected from various related literature sources such as books, journals and online articles. The research results show that nonlinear functions play an important role in various aspects of daily life. From personal financial planning to macroeconomic policy, a good understanding of nonlinear functions and their application to mathematical economics can provide significant benefits to individuals and society as a whole. In addition, this research also highlights the importance of economic mathematics education in helping people understand and apply these concepts in everyday life